1996
DOI: 10.2307/1511249
|View full text |Cite
|
Sign up to set email alerts
|

Views of Students with Learning Disabilities of their Homework in General Education Classes: Student Interviews

Abstract: This study examined the experiences and views of students with learning disabilities regarding the homework they receive in their general education classes and identified ways that teachers and parents might positively affect students' performance. Subjects were 10 high school students identified as having learning disabilities. Individual interviews were conducted to elicit information from each student. An analysis of the interviews resulted in the emergence of three themes: (a) factors that make homework ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
7
0
2
Order By: Relevance
“…This may be attributable to creating universal expectations for the group as opposed to isolating students for individualized services. Students’ perception of stigmatization is a significant predictor of student response to academic adaptations (Bryan et al, 2001; Sawyer et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be attributable to creating universal expectations for the group as opposed to isolating students for individualized services. Students’ perception of stigmatization is a significant predictor of student response to academic adaptations (Bryan et al, 2001; Sawyer et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Teachers did not endorse lowering evaluation standards, adjusting due dates, and giving fewer assignments (Struyk & Epstein, 1995). Students with LD also prefer additional teacher assistance compared to altered assignments because of perceived stigmatization when not held to the same standards as their peers (Bryan et al, 2001; Sawyer, Nelson, Jayanthi, Bursuck, & Epstein, 1996).…”
Section: Homework In School Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Although research supports the belief that parental involvement in their children's homework has a positive effect (Sawyer, Nelson, Jayanthi, Bursuck, & Epstein, 1996), other researchers have expressed concerns about the possible negative influences of parental involvement on children's achievements and attitudes (Cooper, 1989;Levin et al, 1997;Perkins & Milgram, 1996). Perkins and Milgram observed that homework can be a double-edged sword "having a positive influence, or [being] destructive and damaging, to achievement and attitude" (p. 197).…”
Section: Homeworkmentioning
confidence: 99%
“…Homework assignments account for 20% of students' academic engaged time (Cooper & Nye, 1994) Parents describe children with LD as more likely to procrastinate, needing reminders and prompts, and easily distracted during the homework process (Polloway, Epstein, & Foley, 1992) Students with LD report that assignments are made more difficult by teachers when: (a) inconsistent language is used, (b) homework explanations are lacking or too rapid, (c) teachers fail to answer students' questions, (d) homework due dates are not specified, and (e) several assignments are given at once (Sawyer, Nelson, Jayanthi, Bursuck, & Epstein, 1996) The single best indicator of academic achievement among students with educational disabilities may be time actively engaged in learning activities (homework; O'Melia & Rosenberg, 1994) Student achievement is higher when parents monitor homework, participate in school activities, and support the work and values of school (Epstein, 1984) Teachers report the purposes of homework to be: (a) to finish class work, (b) to practice and reinforce class work, and (c) to inform parents about class work (Bryan & Nelson, 1994;Polloway, Epstein, Bursuck, Jayanthi, & Cumblad, 1994) Not being given homework or not being able to do homework with peers may be stigmatizing for students with LD (Vaughn, Schumm, & Kouzekanani, 1993) Types of effective parent involvement vary by age of students: Language deficits may affect students' skillfulness in comprehending assignments, accurately recording them, or communicating them to parents.…”
Section: Homework Problemsmentioning
confidence: 99%